TRAFFICKING CRIME PREVENTION POLICIES FROM A PHILOSOPHICAL, SOCIOLOGICAL, AND JURIDICAL PERSPECTIVE - Sri Wulandari (Universitas 17 Agustus 1945 Semarang, 2022)
The article was written to analyze the policy of overcoming the crime of trafficking as regulated in Law no. 7 of 1984 concerning the Ratification of the Convention on the Elimination of All Forms of Discrimination and Law no. 21 of 2007 concerning the Crime of Human Trafficking (Trafficking). Human trafficking is a criminal act and violates human rights. Considering that Indonesia is the country of origin for the victims of human trafficking, the number of which is quite large, it is necessary to follow up with instruments in the form of prevention and the provision of criminal sanctions. This article addresses two questions: First, how is the legal protection for women and children victims of human trafficking? Second, what is the policy for dealing with trafficking crimes from a philosophical, sociological, and juridical perspective? This article concludes that the crime of human trafficking often occurs in vulnerable groups, namely women and children (victims), motivated by economic, social, and cultural factors. Efforts to protect victims’ rights have been carried out even though they have not been optimal through the prevention and prosecution of perpetrators. Law enforcement against the crime of trafficking is carried out with the concept of punishment and providing compensation/restitution to victims and/or their families. Trafficking is a transnational crime, so handling crimes needs to be done bilaterally/multilaterally. In addition to prioritizing penal facilities, it is necessary to seek non-penal means, involving the community in preventing and overcoming crime through preventive and repressive efforts.